Caspase‐4 mediates non‐canonical activation of the NLRP3 inflammasome in human myeloid cells. Issue 10 (6th August 2015) - Schmid‐Burgk, Jonathan L.; Gaidt, Moritz M.; Schmidt, Tobias; Ebert, Thomas S.; Bartok, Eva; Hornung, Veit
<x xml:space="preserve">Abstract</x> Inflammasome activation culminates in activation of caspase‐1, which leads to the maturation and subsequent release of cytokines of the interleukin 1 (IL‐1) family and results in a particular form of cell death known as pyroptosis. In addition, in the murine system, a so‐called non‐canonical inflammasome involving caspase‐11 has been described that directly responds to cytosolic LPS. Here, we show that the human monocytic cell line THP1 activates the inflammasome in response to cytosolic LPS in a TLR4‐independent fashion. This response is mediated by caspase‐4 and accompanied by caspase‐1 activation, pyroptosis, and IL‐1β maturation. In addition to caspase‐4, efficient IL‐1β conversion upon intracellular LPS delivery relies on potassium efflux, NLRP3, ASC, and caspase‐1, indicating that although caspase‐4 activation alone is sufficient to induce pyroptosis, this process depends on the NLRP3 inflammasome activation to drive IL‐1β maturation. Altogether, this study provides evidence for the presence of a non‐canonical inflammasome in humans and its dependence on caspase‐4.